THE EFFECT OF COBALT CONTENT ON MAGNETIC PROPERTIES OF CoFe ALLOYS - Widia Nursiyanto; L. Rohman; M. Alfatun N.; E. Purwandari (Program Studi Fisika Universitas Negeri Jakarta, 2020)
Hard Disk Drive (HDD) as a data storage device when operated with high temperatures (around 66oC), its function will be constrained. The CoFe alloys have a large coercivity field and can be patterned in very small sizes that are suitable for HDD devices. In this study, Co1-x Fex cube alloy was used (x = 0.25; 0.30; 0.50; 0.75). Samples were treated with temperature changes to get the Curie temperature. The coercivity field value is obtained by giving the external field and temperature below Curie temperature and also above Curie temperature to the samples. The VAMPIRE software is a micromagnetic simulation program based on atomistic models. The results showed that Curie’s temperature decreased when Co content increased. The composition of Co0.25 Fe0.75 has the highest Curie temperature that is equal to 1075 K. The temperature Curie is not affected by the size of the cube. When the sample is given a temperature rise below the Curie temperature, the value of the coercivity field decreases. The value of the coercivity field is very difficult to determine when the temperature used is above the Curie temperature. The percentage of composition does not affect the coercivity field value. Therefore, cube-shaped CoFe material is very suitable for use as a material data storage device operated at temperatures below the Curie.